Dziedziczka imperium (Katarzyna Aleksejewna 1725–1727) - Chojnicka, Krystyna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
This article is devoted to a little known piece of Russian history, namely the years of Catherine I’s reign. Catherine I was the second wife of Peter the Great, who succeeded her husband to the throne in accordance with the Law of Succession of 1722, which introduced a principle unknown in other European countries, whereby each reigning monarch nominated his own successor. The article explains the circumstances – which do not entirely accord with the aforementioned statute – surrounding Catharine’s ascension to the throne, as well as the most important developments connected with her short reign (1725–1727). These years were, to a considerable degree, decisive in sealing the fate of Peter the Great’s plans to create a new, major political power in Europe. The article focuses on the issues connected with the empress, the struggles between the factions that surrounded her, the attempts to restrict and support the power of the empress by a newly founded body – the Supreme Privy Council, and the prevailing economic crisis. Often disregarded in historical literature, the reign of Catherine I, the first in a line of female empresses who built the mighty Russian empire in the eighteenth century, in this context proves key to the history of that state
Keywords: Catherine I (1684-1727); Russia; empire; autocracy; empress; succession to the throne